Owls, Climates, and Experts - Munroe, Robert L. (Journal of cognition and culture, 2018)
The cognitive research of Atran and Medin (2008) plus preliminary cross-cultural inquiry about owls permitted the formulation of a hypothesis: Inhabitants of cold-climate societies were likely to be, in relative terms, “experts” on owls. Subsequent cross-cultural study (N = 56) affirmed that in cold-climate societies, in contrast to others, the habits and characteristics of owls were more frequently noted, these birds were more often used functionally (especially for feather-ornamentation), and the human inhabitants of cold-climate areas manifested fewer negative supernaturalistic interpretations of owl behavior. For the sample as a whole, however, some form of magico-religious belief — usually negative, such as association of owls with witchcraft — exceeded all other practices and concepts, including functional uses and ethnozoological descriptions of owls. The importance of taking affective factors into account in cross-cultural cognitive research was emphasized. Exploratory analysis also revealed that owls were of extraordinarily high interest to Native North Americans, and reasons for this regularity were considered. The paper concludes with discussion of the relation between ecological setting and cultural conceptions of the natural world.